CPU and eGPU Support System Based on Naive Bayes Classification - Mursyid Ardiansyah; Wahyu Hidayat; Ema Utami; Suwanto Raharjo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2021)
Central Processing Unit (CPU) and External Graphics Processing Unit (eGPU) technology are known as overclocks which aim to make the device exceed the benchmarks set by the device maker. Until now there is no determination to rank the two hardware within certain limits such as hardware price range and year-by-year. Therefore, it is necessary to process the ranking of the hardware using Simple Additive Weighting (SAW) to obtain a ranking range and determine the weight per type of hardware analyzed. It can be classified using Naïve Bayes to determine results of criteria combination between two hardware to determine possible criteria into